2006
DOI: 10.1074/jbc.m600776200
|View full text |Cite
|
Sign up to set email alerts
|

Functional Cross-modulation between SOCS Proteins Can Stimulate Cytokine Signaling

Abstract: SOCS (suppressors of cytokine signaling) proteins are negative regulators of cytokine signaling that function primarily at the receptor level. Remarkably, in vitro and in vivo observations revealed both inhibitory and stimulatory effects of SOCS2 on growth hormone signaling, suggesting an additional regulatory level. In this study, we examined the possibility of direct crossmodulation between SOCS proteins and found that SOCS2 could interfere with the inhibitory actions of other SOCS proteins in growth hormone… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
80
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 99 publications
(88 citation statements)
references
References 58 publications
6
80
0
Order By: Relevance
“…For example, it is clear that SOCS2 is a key player in normal GH feedback inhibition since Socs2 −/− mice exhibit gigantism and are 30-40% larger than normal littermates [44] [45]. However, there are other layers of complexity since SOCS proteins can also target SOCS proteins for degradation [46]. Thus, Socs2Tg mice that over express SOCS2 are not dwarf mice but instead are also larger than normal littermates [47] [48].…”
Section: Suppressor Of Cytokine Signaling (Socs) Proteinsmentioning
confidence: 99%
“…For example, it is clear that SOCS2 is a key player in normal GH feedback inhibition since Socs2 −/− mice exhibit gigantism and are 30-40% larger than normal littermates [44] [45]. However, there are other layers of complexity since SOCS proteins can also target SOCS proteins for degradation [46]. Thus, Socs2Tg mice that over express SOCS2 are not dwarf mice but instead are also larger than normal littermates [47] [48].…”
Section: Suppressor Of Cytokine Signaling (Socs) Proteinsmentioning
confidence: 99%
“…Indeed, it has been shown that chemokine CXC ligand-5 induces insulin resistance mainly by inhibiting insulin signalling in muscle, which may be driven by SOCS-2 production [36]. Moreover, a given SOCS protein appears to promote the proteasomal degradation of other SOCS proteins [37]. This suggests that SOCS proteins are able to transregulate the expression of other members of the family, leading to auto-regulatory compensatory mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…An additional level of complexity demonstrated by SOCS proteins is their ability to interact with other SOCS family members (Piessevaux et al, 2006;Tannahill et al, 2005). For example, although SOCS2 plays a major role in the negative regulation of GH signaling (Greenhalgh et al, 2002), it has also been shown to enhance GH signaling.…”
Section: Socs Proteins As Regulators Of Other Tyr Phosphorylation-depmentioning
confidence: 99%